1986
DOI: 10.1093/bja/58.11.1229
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Release During the Administration of Atracurium or Vecuronium in Children

Abstract: The histamine releasing potential of equivalent bolus doses of atracurium 0.6 mg kg-1 or vecuronium 0.12 mg kg-1 was evaluated in 20 children anaesthetized with halothane. Blood samples were obtained before, and at 2 and 5 min after the administration of the neuromuscular blocker. The twitch response to 0.15 Hz was also evaluated. None of the 10 patients receiving vecuronium had a significant increase in plasma histamine concentration. In two of the 10 children receiving atracurium, the plasma histamine concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This has also recently been reported for higher doses of these drngs. 9 The shorter duration of vecuronium may also retlect the use of a less than equipotent dose of the drug. The ED95 of 35 izg.kg -L adopted for this study has also been reported as high as 64 jxg'kg-t using a single dose technique ~~ and also, using a cumulative method, 56 ~g-kg-t. 2 The recovery time to TI/Tc 25 per cent for atracurium 0.4 mg-kg -I, under similar anaestheiic conditions, using EMG monitoring has been reported as 23 minutes t3~4 but, in other studies, as long as 37.6 minutes z which is similar to our finding of 39 37.5 minutes.…”
Section: Atracurium D-tubocnrarine Pancuronium Vet~roni~mmentioning
confidence: 99%
“…This has also recently been reported for higher doses of these drngs. 9 The shorter duration of vecuronium may also retlect the use of a less than equipotent dose of the drug. The ED95 of 35 izg.kg -L adopted for this study has also been reported as high as 64 jxg'kg-t using a single dose technique ~~ and also, using a cumulative method, 56 ~g-kg-t. 2 The recovery time to TI/Tc 25 per cent for atracurium 0.4 mg-kg -I, under similar anaestheiic conditions, using EMG monitoring has been reported as 23 minutes t3~4 but, in other studies, as long as 37.6 minutes z which is similar to our finding of 39 37.5 minutes.…”
Section: Atracurium D-tubocnrarine Pancuronium Vet~roni~mmentioning
confidence: 99%
“…Electronic searches yielded 6345 potentially relevant trials, of which 71 (48 RCTs and 23 CCTs) eligible research papers (Figure 1 and Table S1) were identified, encompassing 4319 in the large majority ASA I‐II pediatric participants in 232 study arms 43–112 . We incorporated three RCTs that enrolled only a few ASA III patients 62,64,83 .…”
Section: Resultsmentioning
confidence: 99%
“…For the comparative outcome analysis of t25, a 26‐node treatment network was produced from 48 studies (41 RCTs and 7 CCTs) with 164 study arms, including 3224 pediatric participants 43–90 …”
Section: Resultsmentioning
confidence: 99%
“…Cardiovascular reactions after administration of atracurium are still controversial, being classified differently by various investigators. Several investigators found no significant cardiovascular changes with doses of atracurium 0.2-0.4 mg kg" 1 [3,21,22,26] and in isolated cases even with 0.5 mg kg" 1 [27]. Dose dependence was investigated further by Hilgenberg and Stoelting using atracurium 0.2 and 0.4 mg kg" 1 [21], Scott and colleagues using 0.6 and 0.8 mg kg" 1 [18,19] and by Tryba and colleagues [1], as mentioned above.…”
Section: There Was No Difference Between Groups In Age Height Weighmentioning
confidence: 99%